Exploring EFL Secondary English Club Students’ Challenges of the Use of British Accent in Speaking Classroom - Muzaki, Muhammad Fariz (English Language in Focus (ELIF), 2024)
Exploring EFL Secondary English Club Students' Challenges with the Use of British Accent in Speaking Classroom is the focus of this study. One of the more challenging accents that students can master in English club is the British accent. The learner can discuss their difficulties in the speaking classroom while using a British accent. This study used an approach with an interview as part of its descriptive qualitative methodology. Three English club students from a vocational high school in Jakarta participated in this study. Nine interview questions helped gather the data for this study. The goal of this study is to examine the difficulties that EFL Secondary English Club Students face when using a British accent in speaking classes. The researcher draws the conclusion that the student's difficulties employing a British accent are constructive based on the findings of the data analysis. The student who uses a British accent in the speaking class presents the most challenge. According to the interview questions, the students approve of the obstacles associated with the British accent in speaking classes. The students respond favorably to the difficulties.